Cartilage degradation in temporomandibular joint induced by unilateral anterior crossbite prosthesis. (25th April 2013) - Wang, Y‐L; Zhang, J; Zhang, M; Lu, L; Wang, X; Guo, M; Zhang, X; Wang, M‐Q
<x xml:space="preserve">Abstract</x> Objective To investigate the pathological effects on temporomandibular joint cartilage of an experimentally created unilateral anterior crossbite prosthesis. Methods Six‐week‐old female Sprague–Dawley rats were divided into experimental and control groups and further divided into three subgroups for three time points (n = 9). In experimental groups, the unilateral anterior crossbite was created by bonding two metal tubes on left maxillary and mandibular incisors. 2, 4, or 8 weeks after operation, the histomorphological changes and the expression changes of PCNA, COL II, aggrecan, MMP‐3, MMP‐9, MMP‐13, and TIMP‐1 in condylar cartilage were investigated by hematoxylin–eosin and toluidine blue staining, real‐time PCR, and immunohistochemistry. Results In experimental groups, decreasing in chondrocytes, cell‐free areas, reduction in the thickness of hypertrophic layer, and loss of extracellular matrix were noticed. The expression level of PCNA was decreased at week 2 and week 4. The mRNA expression of COL II was decreased at 4 week and that of aggrecan was increased at 2 week but decreased at 4 and 8 week. The expression of MMP‐9, MMP‐13, and TIMP‐1 was increased at 2‐week and decreased at 4‐ and 8‐week, while that of MMP‐3 was increased at 4‐ and 8‐week. Conclusions The present unilateral anterior crossbite prosthesis led to degradation of mandibular condylar cartilage.